RISK FACTORS FOR THE INCIDENCE OF ANEMIA IN YOUNG WOMEN: Faktor Risiko Kejadian Anemia Pada Remaja Putri - Nanda Agustian Simatupang; Ummi Kalsum; Adelina Fitri; Dilma'aarij Agustia (Universitas Airlangga, 2023)
Background: The prevalence of anemia in adolescents is still high in Jambi Province at 60.45%. Anemia can cause a decrease in body resistance and fitness, thereby inhibiting adolescent productivity. Purpose: Research objectives to determine the prevalence of anemia and risk factors for the incidence of anemia in young women. Methods: Cross-sectional research design, located in State Senior High School 8 of Jambi City from January to April 2019. Population 552 girls, with a sample of 83 girls in classes X and XI. The proportioned stratified random sampling technique was taken. The research variables were knowledge, breakfast, tablets, blood consumption, nutritional status, enhancing foods and iron absorption inhibitors, infectious diseases, and heavy meal frequency. The dependent variable was anemia. Interviews and secondary data from the measurement of Hb were conducted for primary data collection. Data would be analyzed with chi-square analysis. Results: The incidence of anemia among young women was 42.17%. There was relationship of knowledge (PR=2.05; 95% CI=1.30-3.24), blood tablet supplementation (PR=2.95; 95% CI =1.02-8.54), Breakfast (PR=3.03; 95% CI=1.41-6.48), and frequency of heavy eating (PR = 0.52; 95% CI=0.28-0.97) with the incidence of anemia. Conclusion: Factors associated with anemia among young women are knowledge, consumption of tablets plus blood, breakfast, and frequency of heavy eating.